1999
DOI: 10.1159/000020898
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin’s Disease during Pregnancy: Diagnostic and Therapeutic Management

Abstract: Objectives: To evaluate the possibility that women affected by Hodgkin’s disease (HD) during their second or third trimester of pregnancy can safely carry their pregnancy to term. Methods: From 1986 to 1997, 6 women came to our Center during the second trimester of pregnancy and were diagnosed as having HD. Three of these 6 patients were treated with chemotherapy before delivery and 3 of them were kept under observation and started treatment after delivery. Results: All 6 women gave birth to a healthy female. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 9 publications
0
23
1
2
Order By: Relevance
“…36 Infants born to women with HD during pregnancy do not have a higher risk for prematurity or intrauterine growth retardation. 36 In the cases reported by Anselmo et al, 37 pregnant women affected by HD safely carried their pregnancies to term and gave birth to healthy children. The association of HD with pregnancy is not, on its own, an indication for a therapeutic abortion.…”
Section: Hodgkin's Diseasementioning
confidence: 97%
“…36 Infants born to women with HD during pregnancy do not have a higher risk for prematurity or intrauterine growth retardation. 36 In the cases reported by Anselmo et al, 37 pregnant women affected by HD safely carried their pregnancies to term and gave birth to healthy children. The association of HD with pregnancy is not, on its own, an indication for a therapeutic abortion.…”
Section: Hodgkin's Diseasementioning
confidence: 97%
“…The remaining studies found little, if any, detrimental effect on birth outcome among women capable of becoming pregnant (Andrieu and Ochoa-Molina, 1983;Aisner et al, 1993;Brierley et al, 1998). Likewise, a few case series found normal birth outcome in women diagnosed with HD during or shortly after pregnancy (Woo et al, 1992;Anselmo et al, 1999;Aviles and Neri, 2001). …”
mentioning
confidence: 99%
“…For non-pregnant HL, ABVD regimen is still considered the standard of care (56). Moreover, this regimen has been shown safe and effective at any gestational time and at any stage of disease (3,4,6,53,59,61) inducing Bachanova and Connors (53) to suggest this regimen as the recommend choice (grade lC recommendation) in pregnant HL patients who have to be treated promptly. The safety and effectiveness of ABVD regimen were confirmed also in a small series of pregnant patients with HL and concomitant HIV infection (62).…”
Section: Hodgkin Lymphomamentioning
confidence: 99%